2023
DOI: 10.1186/s12894-022-01172-8
|View full text |Cite|
|
Sign up to set email alerts
|

Prognostic nomogram for overall survival in upper urinary tract urothelial carcinoma (UTUC) patients treated with chemotherapy: a SEER-based retrospective cohort study

Abstract: Objective To establish a prognostic nomogram among UTUC patients who received chemotherapy. Methods 1195 UTUC patients who received chemotherapy were extracted from the Surveillance, Epidemiology, and End Results (SEER) database for the period between 2004 and 2015. Patients were randomly divided into a training and a validation set. Nomogram was constructed to predict 1-, 3-, and 5-year overall survival (OS) in those patients. Receiver-operating … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…The 5-year cancer-specific survival (CSS) in non-muscle-invasive UTUC is 86%, while for muscle-invasive disease, it is 70%. About 9% of patients present with metastatic disease, with a CSS of 39% [75,76]. Our patient was considered a suitable candidate for this surgery, benefiting from a favorable prognostic profile at the initial presentation.…”
Section: Prognosismentioning
confidence: 90%
“…The 5-year cancer-specific survival (CSS) in non-muscle-invasive UTUC is 86%, while for muscle-invasive disease, it is 70%. About 9% of patients present with metastatic disease, with a CSS of 39% [75,76]. Our patient was considered a suitable candidate for this surgery, benefiting from a favorable prognostic profile at the initial presentation.…”
Section: Prognosismentioning
confidence: 90%
“…Another meta-analysis on post-operative nomograms revealed a significant negative predictive value of age for CSS [1]. Although several studies have shown the association between age and survival indices [43,44], no association was found after adjustment for performance status (PS) [45]. However, age is found to be a predictor of muscle-invasive disease [46][47][48][49].…”
Section: Age and Sexmentioning
confidence: 99%
“…The AUC values of 78.9%, 77.2%, and 76.3% show discrimination accuracy of their nomogram for 1-, 3-, and 5-year OS in the development cohort. Their internally validated nomogram showed superior accuracy compared to the American Joint Committee on Cancer (AJCC)-TNM staging system [44].…”
Section: Post-operative Predictive Toolsmentioning
confidence: 99%